The content, the nature of the labor costs of the doctor and their duration when restoring the integrity of the dental arches with splints and tooth with plastic restorations - Ishchenko, P. (Actual Dentistry, 2018)
Summary. The article describes the clinical process of providing orthopedic and therapeutic dental care with chronometric measurements of stages and subsequent processing of results. Recommendations for the development of normative legal acts are given. Key words: splinting, restoration of teeth, labor costs.